A comparative study of different acceleration sensors in measuring energy consumption of human martial arts - Qixia Jia; Zengyin Yan; Yongyong Wang (EURASIP journal on advances in signal processing, 2021)
Abstract At present, there are many acceleration sensors for measuring human martial arts in the market. However, due to the inaccurate measurement of some acceleration sensors, people who love martial arts are deeply troubled and unable to find an excellent acceleration sensor specifically for energy consumption detection of human martial arts. The development of this sensor is imminent, which is of great significance for the comparative study of energy consumption measurement of human martial arts in our country. In this study, 160 students aged 11–14 years were selected, and the subjects were divided into normal body mass group and abnormal body mass group. Of the 96 male adolescents, 32 were obese body mass, which was determined as male abnormal body mass Group; 64 male adolescents were normal body weight and male normal body weight group; female 64 adolescents were normal body weight and set as female normal body mass group. Using a built-in accelerometer and a mobile phone three-dimensional accelerometer, the subjects were subjected to a 3–8 km/h human martial arts exercise load test (each speed is continuously performed for 5 min). The two acceleration sensors collectively assess the accuracy of the prediction of the use of force in human martial arts experiments. The average power consumption of human art exercises uses a frequency of 60 times/min, 90 times/min and 120 times/min compared to two acceleration sensors. Test results show that the data points for the mobile accelerator eraser are scattered, and the distance between the data varies. The data points of the three-dimensional acceleration sensor are more concentrated and present a certain trend. The use of three-dimensional acceleration sensors to measure martial arts can fully reflect the energy consumption of human activities, and achieve an energy consumption measurement accuracy of more than 94%.